Protection of Consumer Data on Digital Services in The Perspective of International Law and National Law - Sari, Febilita Wulan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Covid-19 pandemic has implications for the community, namely the use of digital services to fulfill daily needs. This research aims to find the legal aspects of consumer data on digital services in the international law and national law, and how it is applied in Indonesia. This research uses analytical descriptive method with a juridical normative approach. The result of this research show that international law has various regulations in the form of hard law and soft law that regulate the protection of consumer data in digital service activities, including Article 17 of the International Covenant on Civil and Political Rights (ICCPR) 1966. Consumer protection in the national legal system is guaranteed by Article 4 Law Number 8 of 1999 concerning Consumer Protection, however, consumer data protection in digital services has not been optimally implemented because the law does not yet cover data protection. The guarantees stipulated in the Consumer Protection Law are information about goods and services, not information regarding consumer data. Data obtained from digital services is sometimes misused or transferred to other unauthorized parties. Encouraging the renewal of national provisions regarding consumer protection given the current developments in the digital era that make consumer data vulnerable.